The Study of Speaking Problems Faced by English Department Students of UNP in Doing Group Presentation - Agustian, Faldi; Kher, Dinovia Fannil (Universitas Negeri Padang, 2024)
Speaking was one of the essential components in learning English as a second or foreign language. It was undeniable that many EFL learners need help with speaking performance. This research aimed to explore English Department students’ speaking problems. The research focused on speaking problems related to psychological and group work aspects. The data for this research was gained from students' responses to the distributed questionnaire. Last year English Education and English Literature students in the English Department UNP were chosen as the population. The sample consisted of 67 students selected through a simple random sampling technique. The data was analyzed using descriptive method with simple statistics. The findings of the research showed the speaking problems faced by students were related to anxiety, lack of confidence, fear of making mistakes, shyness, and group work problems.